Volatile components of Discaria americana Gillies & Hook (Rhamnaceae) - Rodriguez, Silvana Andrea (2008)
The volatile fraction from aerial parts (flowers, stems and leaves) of Discaria americana Gillies & Hook (Rhamnaceae) was obtained by hydrodistillation and the chemical composition of this oil was determined by gas chromatography and gas chromatography-mass spectrometry. The major constituents resulted to be 4-methylphenol (15.5%), eugenol (11%), 3-methylindole (9.7%) and α-terpineol (6.2%). The essential oil of this plant displayed strong antioxidant activity (DPPH assay) that could be explained by the presence of active compounds like eugenol, 4-methylphenol, α-terpineol, linalool, thymol and cis-nerolidol.